Blaming "the other": Predicting collective guilt in Croatian and Serbian sample - Penić, Sandra; Vasović, Mirjana; Gligorijević, Milena; Čorkalo Biruški, Dinka (2008)
After the war relations among former adversaries are heavily burden by atrocities that have been done during the conflict. As a consequence of severe victimization, individual and collective, there is a tendency on the opposite sides to blame not individuals but the whole adversary group for what happened in the past. The aim of the present study was to identify a set of predictors of the collective guilt, taking into account contextual differences in two countries that recently fought the war. We measured objective traumatic experiences, experiences of perceived injustice, ethnic identification, and social distance towards the former adversary and non-adversary groups, taken as a measure of ethnic prejudice. 390 adult Croats from 17 regions in Croatia and 346 adult Serbs from 19 regions in Serbia and Monte Negro participated in the study. By using the multilevel analysis a model for predicting collective guilt has been developed. On the individual level traumatic experiences were not predictive for blaming the whole group ; the significant predictors were the experiences of perceived injustice, ethnic identification and social distance toward the adversary group. However, the group level analysis indicates the regional variations in relations between the ethnic identification and the collective guilt as well as between the perceived injustice and collective guilt, depending on the level of the collective guilt that was attributed to the adversary group. The relationship between ethnic prejudice and perceived group accountability also varied regionally. Results will be discussed by taking into account both individual and contextual factors in explaining collective guilt.
Projekt MZOS
ENG